Investigating Environmental Health Engineering Graduates' Attitudes towards Compliance of the Received Trainings with their Occupational Needs in Mashhad, Iran, 2019 - Roya Peirovi; Sara Javanbakht; Zohre Moeini; Monnavar Afzal Aghaee; Hossein Alidadi (Shiraz University of Medical Sciences, 2021)
Introduction: One of the most important goals of any higher education system is to educate specialized manpower with sufficient skills and knowledge. Therefore, this study was conducted to investigate the environmental health engineering graduates' attitudes towards compliance of the received training during their education with their occupational needs. Methods: In this descriptive study, the viewpoints of 76 environmental health engineering graduates were investigated over the compliance of the contents of the courses passed with their occupational needs. The participants were employed in various organizational positions in Mashhad city in 201‪9. Data extracted from the questionnaires were analyzed using one-way ANOVA and independent t-test. Results: In the case of Water and Wastewater, Municipality, Comprehensive Health Center, Hospital, and Common courses, the lowest compliance rate was related to the environmental health employees working at the comprehensive health centers, hospitals, water and sewerage company, and university, respectively. There was a significant difference between attitudes of males and females towards Water and Wastewater and Comprehensive Health Center courses. Findings based on the graduates' degrees showed that people with bachelor's degrees more disagreed with the set of Water and Wastewater courses than the graduates with Master's and Ph.D. degrees. Conclusion: Considering that specialized courses had the highest compliance with the individuals' field of work, the authorities are recommended to revise the curriculum of this field of study. Furthermore, it is  suggested that specialized trends in the undergraduate course should be provided to improve the impact of education and graduates' satisfaction rate in this field.